The Role of Monetary Compensation in Employee Retention within Contemporary Workplaces: A Quantitative Study - Shakya, Mila; Dongol, Padam (Journal of Kathmandu BernHardt College, 2025)
This study investigates the impact of monetary compensation on employee retention, with a focus on key financial factors such as salary, performance-based bonuses, and allowances. Using a quantitative research design, data were collected from 385 employees of e-Sewa Private Limited and e-Sewa Money Transfer through structured questionnaires, selected using a random sampling technique. Statistical analyses, including descriptive statistics, correlation, and regression, were performed using SPSS. The demographic profile revealed that female employees aged 25–35, particularly those with higher education and IT backgrounds, were most influenced by monetary compensation. The findings highlight that performance-based bonuses exert the strongest influence on employee retention as they directly link financial rewards to individual contributions and achievements. Salary increments and allowances also showed a positive effect on job satisfaction and retention, though to a lesser extent. Overall, regression results confirmed that the independent variables explained 96.1% of the variation in employee retention. The study concludes that timely, fair, and competitive compensation practices are critical for fostering employee loyalty. It further suggests integrating non-monetary rewards such as career development opportunities and recognition initiatives to strengthen engagement and sustain retention in modern workplaces.